Prime Minister's Decree No. 42 of the Year 2017 On Determining The Technical And Financial Requirements That must be met by Investors To Whom The Developed Industrial Lands at the Governorates Of Upper Egypt May be allocated Free of Charge = قرار مجلس الوزراء رقم 42 لسنة 2017 بشأن تحديد الشروط الفنية والمالية الواجب توافرها فى المستثمرين الذين يجوز التصرف لهم فى الأراضى الصناعية المرفقة بمحافظات الصعيد بدون مقابل - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic